2017
DOI: 10.3390/healthcare5040092
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hemodialysis on Spatio-Temporal Characteristics of Gait and Role of Exercise: A Systematic Review

Abstract: Background: People with end-stage kidney disease (ESKD) on hemodialysis (HD) commonly have functional impairments. The purpose of this systematic review was to evaluate the effect of HD on spatio-temporal characteristics of gait, and effect of exercise on these parameters. Methods: Electronic databases were searched to identify relevant citations. Extracted data was computed using a random effects model for means (Hedges’ and 95% confidence interval (CI). Results: 27 studies met inclusion criteria. Mean values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(137 reference statements)
1
3
0
Order By: Relevance
“…The walking velocity of the hemodialysis group was 1.14 ± 0.18 m/sec, and the walking rate was 119.9 ± 10.1 steps/min. Previous studies of the walking parameters of hemodialysis patients reported that the walking velocity was 1.01 m/s [29], and the walking rate was 100.1 ± 12.6 steps/min [30]. In our hemodialysis group, the walking velocity was relatively maintained, and the walking rate was higher.…”
Section: Gait Parameterssupporting
confidence: 41%
“…The walking velocity of the hemodialysis group was 1.14 ± 0.18 m/sec, and the walking rate was 119.9 ± 10.1 steps/min. Previous studies of the walking parameters of hemodialysis patients reported that the walking velocity was 1.01 m/s [29], and the walking rate was 100.1 ± 12.6 steps/min [30]. In our hemodialysis group, the walking velocity was relatively maintained, and the walking rate was higher.…”
Section: Gait Parameterssupporting
confidence: 41%
“…Exercise therapy improves physical function in older patients undergoing dialysis, but the mechanism of benefit may differ from that in middle-aged patients. Previous studies have indicated that exercise therapy for middle-aged hemodialysis patients improved muscle strength [8,31] and the 10-m walking speed [32]. The effect of exercise therapy for advanced-age patients undergoing hemodialysis, as compared with the effect on middle-aged patients, differs across studies.…”
Section: Plos Onementioning
confidence: 99%
“…The gait of Cluster 1 had been on hemodialysis for a longer duration than Cluster 2, was an inflection at the knee joint, ankle joint, and trunk, and the ankle joint plantarflexion moment in Cluster 1 was small at toe-off, resulting in inadequate kicking and a reduced walking rate and walking velocity. The walking velocity of hemodialysis patients was lower than that of the same age group, with a reported walking velocity of 1.01 m/s [27] and a walking rate of 100.1 ± 12.6 steps /min [28].…”
Section: Characteristics Of Walking In Each Clustermentioning
confidence: 74%